Development of Academic Skills Based on Informatic Technologies - Congacha Aushay, Edgar Patricio (2018)
The objective of this research is to observe the impact that the use of educational software with educational strategies within the field of academic aptitude concerning the numerical, verbal and abstract reasoning in education, considering the cognitive theory of instructional design of Robert Gagné, which fosters the development skills and learning skills. It was worked with 175 students in the last year of high school of four educational units in Riobamba city, were evaluated at the beginning and the end of the research, with similar to those applied for college entrance tests. As a result of the investigation it was observed that 155 students increased their score after preparation with the developed software, representing an increase of 94.12% in the score obtained, which allows the conclusion that computer technologies are tools to support the development of academic skills.